Developmental Education for University Students: Ways and Methods of its Organization - Samarokova, Irina V. (2020)
This article is devoted to the organization of developmental education of students of higher educational institutions. Based on works by I.A. Zimniaia, T.I. Iliin, V.V. Kraevskii, G.M. Kodzhaspirova, I.Ia. Lerner, I.F. Kharlamov and other researchers, the authors clarified the concept of “developmental education of university students", analyzed its components, systematized domestic and foreign experience in organizing developmental education in a higher educational institution. The article also presents the author’s set of pedagogical conditions, which contributes to the organization of developmental education for university students. This set includes the following components: correction of students' value orientations in the educational process of the university; the development of cognitive activity of students and the construction of the educational process at the university, subject to the requirements of a person-centered approach.